2000
DOI: 10.1046/j.1432-1327.2000.01552.x
|View full text |Cite
|
Sign up to set email alerts
|

The riboflavin/FAD cycle in rat liver mitochondria

Abstract: Here we provide evidence that mitochondria isolated from rat liver can synthesize FAD from riboflavin that has been taken up and from endogenous ATP. Riboflavin uptake takes place via a carrier-mediated process, as shown by the inverse relationship between fold accumulation and riboflavin concentration, the saturation kinetics [riboflavin K m and V max values were 4.4^1.3 mm and 35^5 pmol´min 21´( mg protein) 21 , respectively] and the inhibition shown by the thiol reagent mersalyl, which cannot enter the mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 46 publications
7
73
0
Order By: Relevance
“…In both rat liver mitochondria (RLM) and Saccharomyces cerevisiae mitochondria, FAD synthesis occurs from ribo£avin and/or FMN due to the existence of a ribo£avin kinase (EC 2.7.1.26) and a FAD synthetase (EC 2.7.7.2). The latter has been characterised from RLM and localised in the mitochondrial matrix [5]. Consistently, ribo£avin kinase, the product of the FMN1 gene in S. cerevisiae, has been found to be localised in the inner mitochondrial membrane [6].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…In both rat liver mitochondria (RLM) and Saccharomyces cerevisiae mitochondria, FAD synthesis occurs from ribo£avin and/or FMN due to the existence of a ribo£avin kinase (EC 2.7.1.26) and a FAD synthetase (EC 2.7.7.2). The latter has been characterised from RLM and localised in the mitochondrial matrix [5]. Consistently, ribo£avin kinase, the product of the FMN1 gene in S. cerevisiae, has been found to be localised in the inner mitochondrial membrane [6].…”
Section: Introductionmentioning
confidence: 78%
“…The mitochondrial matrix actively participates in holoMe 2 GlyDH biogenesis also by providing the £avin cofactor [5,9]. Considering that Me 2 GlyDH is synthesised in the cytosol as a precursor polypeptide, we asked whether mitochondrial component(s) are able to promote holoenzyme formation starting from the precursor.…”
Section: Discussionmentioning
confidence: 99%
“…Bai et al analyzed mtDNA polymorphisms in EuropeanAmerican females and reported that A10398G and T16519C mitochondria involved in the regulation of these complex processes remains elusive. These collectively include SAM, 54 ATP (adenosine triphosphate) citrate lyase (ACL), Acetyl-CoA, 62 flavin adenine dinucleotide (FAD), 63 and lysine-specific demethylase 1 (LSD1). 64,65 Understanding the influence these factors have on epigenetic states of nuclear genomic DNA and signaling pathways could help identify roles bioenergetics, biogenesis and the mitochondria might have in regulating epigenetic modifications within the nuclear genome.…”
Section: Inherited Mtdna Mutations and Predisposition To Cancermentioning
confidence: 99%
“…61 The level of cross talk between DNA methylation and chromatin state are beginning to be identified. An understanding of factors, co-factors and enzymes generated both outside and inside the nucleus and within the 65 The process of H3K4me2 demethylation catalyzed by LSD1 utilizes the classical amine oxidation reaction and FAD as a co-factor 63 ( Fig. 2A).…”
Section: Regulation Of Genomic Dna Methylation and Chromatin Structurmentioning
confidence: 99%
See 1 more Smart Citation